Expanding the Mutation Spectrum in ABCA4: Sixty Novel Disease Causing Variants and Their Associated Phenotype in a Large French Stargardt Cohort - Nassisi, Marco; Mohand-Saïd, Saddek; Dhaenens, Claire-Marie; Boyard, Fiona; Démontant, Vanessa; Andrieu, Camille; Antonio, Aline; Condroyer, Christel; Foussard, Marine; Méjécase, Cécile; Eandi, Chiara; Sahel, José-Alain; et al. (International journal of molecular sciences, 2018)
Here we report novel mutations in ABCA4 with the underlying phenotype in a large French cohort with autosomal recessive Stargardt disease. The DNA samples of 397 index subjects were analyzed in exons and flanking intronic regions of ABCA4 (NM_000350.2) by microarray analysis and direct Sanger sequencing. At the end of the screening, at least two likely pathogenic mutations were found in 302 patients (76.1%) while 95 remained unsolved: 40 (10.1%) with no variants identified, 52 (13.1%) with one heterozygous mutation, and 3 (0.7%) with at least one variant of uncertain significance (VUS). Sixty-three novel variants were identified in the cohort. Three of them were variants of uncertain significance. The other 60 mutations were classified as likely pathogenic or pathogenic, and were identified in 61 patients (15.4%). The majority of those were missense (55%) followed by frameshift and nonsense (30%), intronic (11.7%) variants, and in-frame deletions (3.3%). Only patients with variants never reported in literature were further analyzed herein. Recruited subjects underwent complete ophthalmic examination including best corrected visual acuity, kinetic and static perimetry, color vision test, full-field and multifocal electroretinography, color fundus photography, short-wavelength and near-infrared fundus autofluorescence imaging, and spectral domain optical coherence tomography. Clinical evaluation of each subject confirms the tendency that truncating mutations lead to a more severe phenotype with electroretinogram (ERG) impairment (p = 0.002) and an earlier age of onset (p = 0.037). Our study further expands the mutation spectrum in the exonic and flanking regions of ABCA4 underlying Stargardt disease.